Dirhodium(II)-Mediated Alkene Epoxidation with Iodine(III) Oxidants - Nasrallah, Ali (2018)
Dirhodium(II) complexes and iodine(III) oxidants have found useful applications in synthetic nitrene chemistry. In this study, the combination of the dirhodium(II) complex Rh2(tpa)4 (tpa = triphenylacetate) with the iodine(III) oxidant PhI(OPiv)2 is shown to promote the epoxidation of alkenes in the presence of 2 equivalents of water. The reaction can be applied to diversely substituted alkenes and the corresponding epoxides are isolated with yields of up to 90 %. A possible mechanism involves the dirhodium(II) complex as a Lewis acid species that would tune the oxidizing character of the iodine(III) reagent.